Efficacy of Rg1-Oil Adjuvant on Inducing Immune Responses against Bordetella bronchiseptica in Rabbits - Xiao Chenwen; Ji Quanan; Huang Yee; Liu Yan; Wang Jiaoyu; Wei Qiang; Qiao Litao; Nan Li; Bao Guolian (Journal of Immunology Research)
Bordetella bronchiseptica (B. bronchiseptica) is an obligately aerobic, oxidase- and catalase-positive, nonfermentative Gram-negative coccobacillus. This study is aimed at examining the immune effects of Rg1, Rg1 plus oil, and other common adjuvants on inactivated B. bronchiseptica vaccine in rabbits. The mechanism underlying the adjuvant effect of Rg1 plus oil on the vaccine was also explored. Rg1 (100 μg) plus oil significantly improved the immune effect of B. bronchiseptica vaccine at both the humoral and cellular levels. Rg1-oil adjuvant increased the levels of IL-2 and IL-4 in rabbits after immunization. Rg1 (100 μg) plus oil also significantly increased TLR2 expression and downregulated NF-κB in splenocytes. Rg1-oil adjuvant may increase the levels of IL-2 and IL-4 via upregulating TLR2, thereby enhancing the immune effect of B. bronchiseptica vaccine. In conclusion, Rg1 plus oil could be used as a potential vaccine adjuvant for rabbit B. bronchiseptica vaccine.